Tourism development impact in Redang Island, Malaysia: a stakeholder’s view - Abd Hamid, Abhar Husaini; Abdul Aziz, Yuhanis; Abdullah, Nawal Hanim; Hanafiah, Mohd Hafiz; Abd. Rahman, Azmawani (UNIMAS Publisher, 2024)
Stakeholder perception is a powerful indication for determining the course of tourism development in a tourism site. Stakeholders expressed worries about the environmental effects, socio-cultural changes, and economic consequences of unstructured tourism development on Redang Island. This qualitative study aims to critically examine the stakeholders’ perceptions towards tourism development in Redang Island, Malaysia, focusing on responsible tourism practices. The research also explores the challenges and issues faced in implementing responsible tourism in the area by obtaining feedback from the key stakeholders. A quota sampling approach was employed, resulting in a total of 30 individuals being interviewed in April 2023. Structured, in-depth, face-to-face interviews were conducted to obtain rich and diverse data with regard to the topic. These issues have raised critical questions about the island’s sustainability and imbalance of responsible tourism practices. The interviewees also highlighted the need for a unified foundation for informed decision-making and policy development to promote sustainable and responsible tourism on the island. The study provides a compelling insight into the familiarity of responsible tourism practices from the perspectives of multiple tourism stakeholders within the small island realm. This study strengthens the urge for cooperation from all stakeholders for effective understanding and implementation of responsible tourism practices. This study is among a few to offer a comprehensive analysis of responsible tourism practices in Redang Island by critically examining the stakeholder views and recommendations.